ANALISIS PEMASARAN UDANG VANNAMEI DI DESA BOYANTONGO KECAMATAN PARIGI SELATAN KABUPATEN PARIGI MOUTONG - Arun, Fadlia; Alam, Max Nur; Tangkesalu, Dance (AGROTEKBIS, 2019)
This research intends to identify marketing form of vennamei shrimp, the amount of margin on each marketing channel, price received by farmers on each marketing channel, and marketing efficiency of vennamei shrimp on each marketing channel. This research was conducted on April to July 2017 in Boyatongo village South Parigi sub-district Parigi Mautong Regency. Respondent of sample is farmers and collecting and retailing traders. 12 farmers as the sample was taken through saturated sampling while 2 of collecting traders and 2 of retailing traders was taken through tracing method  so the total number of sample are 16 people. The result of this descriptive research revealed that (i) the marketing form is farmers to collecting traders to retailing traders to consumer, while the second channel showed farmers to collecting traders to exporter. (ii) The result of margin analysis of vennamei shrimp marketing revealed that the first channel is Rp. 5,000/kg and the second channel is Rp. 6,000/kg. (iii) The marketing efficiency showed that the value of marketing efficiency of first channel is 5,24% and the second channel 4,58%.